EXAMINING THE FACTORS THAT LED TO THE REVOLUTION IN THE COUNTRIES THAT WERE ELIMINATED AT BUMN - Mercy Monika R Sitompul; Runtung Sitepu; Faisal Akbar; Ningrum Natasya Sirait (Green Publisher, 2024)
Separated state wealth has been a